PBDEs in cod (Gadus morhua) liver products (1972–2017): Occurrence and human exposure. (October 2019) - Falandysz, Jerzy; Smith, Frankie; Steel, Zoe; Fernandes, Alwyn R.
Abstract: PBDEs occur in a range of commonly consumed foods but there is very little current information on occurrence in dietary supplements such as cod liver oil or cod livers used as food. This study retrospectively investigated a number of these products, sourced from the Baltic Sea and North Atlantic, historically dating from 1972 to 2017. For the sum of 17 measured PBDEs (ΣPBDE), the concentrations ranged from 9.9 to 415 ng g −1 for the oils and from 10.5 to 13 ng g −1 for canned liver products. Concentrations in the oils were highest during the period from 1993 to 2001. For all samples, BDE-47 was the dominant congener with a maximum detected concentration of 308 ng g −1 in a Baltic cod liver oil from 1993. Human exposure to PBDEs from recommended doses were estimated for adults, teenagers and children. Depending on the age group, BDE-47 intakes ranged from 1.3 to 211.5 ng kg −1 bm day −1 (Baltic Sea), 2.9–12.7 ng kg −1 bm day −1 (Atlantic, Norway) and 1.1–4.8 ng kg −1 bm day −1 (Atlantic, Iceland). Intakes for the other dominant congeners, BDE-49, BDE-99 and BDE-100, were relatively low. The intake estimates of ΣPBDE were highest for Baltic cod liver oils ranging from 2.2 to 284.8 ng kg −1 bm day −1 for adults, 2.8–178 ng kg −1 bm day −1 for teenagers and 2.0–127.8 ng kg −1 bm day −1 for a child. Estimated weekly intake of ΣPBDE from canned cod liver was highest for adults, ranging from 17.6 to 25.1 ng kg −1 bm. Highlights: Individual PBDE congener occurrence of >300 ng g −1 in historical medicinal grade cod liver oil. Estimated adult daily intakes of ΣPBDEs from recommended dose – max. 285 ng kg −1 bm day −1 . Canned liver foods from 2017 show ΣPBDE concentrations of 10–13 ng g −1 .